Modern econo[metric] modelling for developing economies 1 - Nwaobi, Godwin Chukwudum (Lagos, Nigeria : Quantitative Economic Research Bureau (Quanterb), 2001)
Modern Econo (metric) modeling presents the applied economist with a variety of difficulties and hence, this book provides assistance in the difficult task of actually constructing models, while alternative strategies are discussed with emphasis on the evaluation of models. This book will be useful to a wide audience of applied and theoretical researchers, graduate students and professional economists.
Includes bibliographical references (p. 270-276) and index.
lje 25/08/16
Loans
Keywords: Econometric modelling; Developing countries; Economic history